2010
DOI: 10.2203/dose-response.09-059.leonard
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Cancer Risks from Radon – Part III - Evidence of Influence of Combined Bystander and Adaptive Response Effects on Radon Case-Control Studies - A Microdose Analysis

Abstract: ᮀ Since the publication of the BEIR VI (1999) report on health risks from radon, a significant amount of new data has been published showing various mechanisms that may affect the ultimate assessment of radon as a carcinogen, in particular the potentially deleterious Bystander Effect (BE) and the potentially beneficial Adaptive Response radio-protection (AR). The case-control radon lung cancer risk data of the pooled 13 European countries radon study (Darby et al 2005(Darby et al , 2006) and the 8 North Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
(365 reference statements)
1
3
0
Order By: Relevance
“…Here we used – cosmic rays 1.00 mSv; Terrestrial gamma 0.60 mSv (U gamma 0.146 mv; Th gamma 0.234 mSv; K-40 gamma 0.220 mSv); internal 0.80 mSv; and medical 1.20 mSv. These large variations support a large variation in human lung cancer risks for the case-control studies shown in Figures 2A and 2B of Part I (Leonard et al 2009a), which are further studied in Part III (Leonard et al 2009b). The normalized alpha particle representative dose response given in Figure 16 of Part I further support a non-linear BaD Model type dose response in the large variations in Figures 16 and 17.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Here we used – cosmic rays 1.00 mSv; Terrestrial gamma 0.60 mSv (U gamma 0.146 mv; Th gamma 0.234 mSv; K-40 gamma 0.220 mSv); internal 0.80 mSv; and medical 1.20 mSv. These large variations support a large variation in human lung cancer risks for the case-control studies shown in Figures 2A and 2B of Part I (Leonard et al 2009a), which are further studied in Part III (Leonard et al 2009b). The normalized alpha particle representative dose response given in Figure 16 of Part I further support a non-linear BaD Model type dose response in the large variations in Figures 16 and 17.…”
Section: Discussionsupporting
confidence: 55%
“…The normalized alpha particle representative dose response given in Figure 16 of Part I further support a non-linear BaD Model type dose response in the large variations in Figures 16 and 17. This will be shown to be true, in Part III (Leonard et al 2009b), for the case-control studies. There is a difference relative to the expected dose response from case-control studies and what we have predicted in Figures 16 and 17 for combined bystander and adaptive response effects.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations